Convents and Change: Autonomy, Marginalization, and Religious Affiliation in Late-Medieval Bologna - Johnson, Sherri Franks (The catholic historical review, 2011)
The histories of two Bolognese monastic houses, Santa Maria del Monte della Guardia and Santa Caterina, reveal the complex relationships between some religious women’s communities and monastic orders. They began as communities in small, regional congregations; became Augustinian in the mid-thirteenth century due to papal intervention; and were Dominican by the fifteenth century. Amid these changes, both communities attempted to retain elements of their early status and practices rather than accepting integration into larger orders. Whereas much scholarly attention rightly has been paid to convents that strove for incorporation into the religious orders, examinations of communities with more fluid affiliations can complement these studies and provide a fuller picture of medieval religious women’s lives.